1982
DOI: 10.1113/jphysiol.1982.sp014417
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and physiological properties of cat motor units after self‐ and cross‐reinnervation

Abstract: SUMMARY1. This report describes selected histochemical and physiological properties of the motor units of adult cat soleus muscle approximately one year after self-and cross-reinnervation with the nerve of the heterogenous flexor hallucis longus (f.h.l.). Self-reinnervated f.h.l. motor units are also considered. Whole muscles were tested for fibre reaction to alkaline pre-incubated ATPase, cz-glycerophosphate dehydrogenase (a-GPD) and reduced nicotinamide adenine dinucleotide diaphorase (NADH-D). Motor units w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…The finding of substantial muscular wasting as a result of virtually complete paralysis lasting 2 or 4 weeks is in accord with a significant role of some factor(s) associated with neuromuscular activity in regulating the mass of rat soleus muscle. The stimulus of active or passive lengthening has also been shown (Goldspink, 1978;Spector et al, 1982) to influence dramatically both MW and F-CSA. Nevertheless, the present results also demonstrate an additional factor that appears to influence muscle mass.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The finding of substantial muscular wasting as a result of virtually complete paralysis lasting 2 or 4 weeks is in accord with a significant role of some factor(s) associated with neuromuscular activity in regulating the mass of rat soleus muscle. The stimulus of active or passive lengthening has also been shown (Goldspink, 1978;Spector et al, 1982) to influence dramatically both MW and F-CSA. Nevertheless, the present results also demonstrate an additional factor that appears to influence muscle mass.…”
Section: Discussionmentioning
confidence: 98%
“…The extreme fluctuations in skeletal muscle mass due to such perturbations as high resistance weight training (Edgerton, 1976) joint immobilization (Solandt et al, 1943;Spector et al, 1982) or spinal cord transection (Johnson et al, 1982;Mayer et al, 1984) are attributed to changes in the pattern (Salmons and Sreter, 1976) or degree (Sreter et al, 1982) of neuromuscular activity. The finding of substantial muscular wasting as a result of virtually complete paralysis lasting 2 or 4 weeks is in accord with a significant role of some factor(s) associated with neuromuscular activity in regulating the mass of rat soleus muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the almost complete transformation usually observed on crossreinnervated fast-twitch muscles is in marked contrast to the very incomplete transformation produced by cross-reinnervation of slow-twitch muscles (Dum et al, 198Sa,b;for review, see Jolesz and SrCter, 1981). Particularly, although contraction time of slow-twitch muscle is faster when cross-reinnervated by a nerve from a fast muscle, this may not be accompanied by change in the histochemical pattern of myosin ATPase activity (Buller et al, 1969;Chan et al, 1982;Gauthier et al, 1983). Thus, the transformations of the biochemical properties do not parallel in every respect those of the physiological ones (SrCter et al, 197.5;Srihari et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Myosin preparation. Myosin was prepared as prey iously described (d 'Albis et al, 1979). Briefly, small pieces of f'rozen muscles previously thawed on ice were washed in five volumes 20 mM NaCl, 5 mM sodium phosphate, 1 mM EGTA, pH 6.5.…”
Section: Methodsmentioning
confidence: 99%